1996
DOI: 10.1086/176814
|View full text |Cite
|
Sign up to set email alerts
|

The Connection between Submillimeter Continuum Flux and Binary Separation in Young Binaries: Evidence of Interaction between Stars and Disks

Abstract: We present 800 µm continuum photometry of pre-main-sequence binary stars with projected separations a p < 150 AU in the Scorpius-Ophiuchus star-forming region. Combining our observations with published 1300 µm continuum photometry from André & Montmerle (1994), we find that binaries in Sco-Oph with 1 < a p < 50-100 AU have lower submillimeter continuum fluxes than wider binaries or single stars, as previously found for Taurus-Auriga binaries. The wide binaries and single stars have indistinguishable submillime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
131
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(147 citation statements)
references
References 40 publications
16
131
0
Order By: Relevance
“…STIS coronagraphic imaging of another Herbig Ae star, MWC 758, suggests that the presence of a candidate companion with luminosity compatible with a brown dwarf some 2A (262 AU) from the primary results in truncation of the disk (e.g., no disk detectable beyond the STIS wedge in tandem with the source being unresolved in the millimeter ; Mannings & Sargent 1997) rather than formation of a dark lane in the disk. Similar results have been inferred for T Tauri stars with companion separations (Jensen et al 1996).…”
Section: Discussionsupporting
confidence: 89%
“…STIS coronagraphic imaging of another Herbig Ae star, MWC 758, suggests that the presence of a candidate companion with luminosity compatible with a brown dwarf some 2A (262 AU) from the primary results in truncation of the disk (e.g., no disk detectable beyond the STIS wedge in tandem with the source being unresolved in the millimeter ; Mannings & Sargent 1997) rather than formation of a dark lane in the disk. Similar results have been inferred for T Tauri stars with companion separations (Jensen et al 1996).…”
Section: Discussionsupporting
confidence: 89%
“…This result is consistent with the observation of reduced millimeter and submillimeter flux from T Tauri binaries with separations less than rv 50-100 AU compared to wider binaries in several star forming regions (e.g. Jensen et al 1996).…”
Section: Binaries and Stellar Rotationsupporting
confidence: 92%
“…Since neither the HD 98800A or Hen 3-600B components are found to harbor any disk material, we subtract their stellar templates from the composite Spitzer IRS spectra for each system (Uchida et al 2004;Furlan et al 2007) to derive the star+disk spectra for HD 98800B and Hen 3-600A alone. Assuming that the emission at longer wavelengths is generated solely by the disks, we include the far-infrared and millimeter photometry from the literature in the SEDs without any such corrections (Jensen et al 1996b;Sylvester et al 1996Sylvester et al , 2001Low et al 2005).…”
Section: Disk Modelsmentioning
confidence: 99%
“…The disks in these systems suffer the most dramatic effects of star-disk interactions, resulting in their external truncation at a fraction of the component separation (∼0.2a-0.5a), or perhaps their complete dispersal. Single-dish radio photometry surveys have demonstrated that the ∼1 mm luminosities for medium-separation binaries are significantly lower than their more closely or widely separated counterparts (as well as single stars; Jensen et al 1994Jensen et al , 1996bOsterloh & Beckwith 1995;Andrews & Williams 2005b). Since the dust emission at these wavelengths is optically thin (Beckwith et al 1990), this luminosity deficit is interpreted as indirect evidence for a diminished disk mass due to the tidal truncation of the outer disk.…”
Section: Introductionmentioning
confidence: 99%